Optic Pathway Gliomas - Beres, Shannon Jeanine; Avery, Robert A. (Journal of Pediatric Neurology, 2017)
Childhood optic pathway gliomas (OPGs) are low-grade neoplasms intrinsic to the precortical visual pathway. These tumors occur preferentially during the first decade of life, especially in children with neurofibromatosis type 1. This review describes our current understanding of OPG pathology and discusses advances in their clinical evaluation, imaging, and management.
Keywords: optic pathway glioma; pilocytic astrocytoma; vision loss; optic atrophy; pediatric